Serum Calprotectin as a Biomarker for Acute Coronary Syndrome: Comparative Analysis with Troponin and C-Reactive Protein - Mansoor, Ali Talib; Al-Nafie, Assad K. H.; Tushy, Akeel Sh.; Sameir, Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Background: Inflammatory biomarkers are widely used in cardiovascular risk assessment; however, their diagnostic and predictive performance varies. This study aimed to compare calprotectin with C-reactive protein (CRP) and troponin regarding their association with clinical outcome and angiographic severity. Methods: Seventy-eight patients were included and categorized into patients (n = 50) and controls (n = 28). According to the results of 37 patients, PCI was noted as positive if the coronary artery lesion was total, subtotal, or significant (70%-90% occlusion). Lesions not meeting these criteria were noted as negative for 13 patients. Serum calprotectin, CRP, and troponin levels were analysed. Normality was assessed using Kolmogorov–Smirnov and Shapiro–Wilk tests. Group comparisons were conducted using the Mann–Whitney U or independent-samples t-test where appropriate. Associations were evaluated using chi-square tests and Spearman correlation. Diagnostic performance was assessed by receiver operating characteristic (ROC) analysis. Results: All biomarkers showed non-normal distributions (p < 0.05). Calprotectin levels were significantly higher in the positive outcome group compared with the negative group (45.15 ± 33.62 vs 14.29 ± 24.42, p < 0.001). CRP and troponin showed no significant differences between outcome groups. Age was significantly associated with angiographic severity (p = 0.005). ROC analysis demonstrated excellent diagnostic accuracy for calprotectin (AUC = 0.809), while CRP and troponin showed poor discrimination. Conclusion: Calprotectin outperforms CRP and troponin as a predictive and discriminatory biomarker, reflecting neutrophil-driven inflammation and plaque instability rather than systemic inflammation or late myocardial injury.